Culture moves : ideas, activism, and changing values - Rochon, Thomas R., 1952- (Princeton University Press, 1998)
Some periods in history are marked by stability in cultural values; at other times, values undergo rapid change. How and why do cultural transformations, such as those affecting race and gender relations, take place? How does one value win acceptance in society when there are conflicting values competing for attention? In Culture Moves, Thomas Rochon addresses this complex process and develops a theory to explain both how values originate and how they spread. In particular, he analyzes the crucial role that small communities of critical thinkers play in developing new ideas and inspiring their dissemination through larger social movements. Rochon develops this theory by drawing from such sources as survey research, content analysis of the mass media, and historical accounts. He focuses mainly on contemporary issues in the United States, such as feminism, civil rights, and environmentalism, but also discusses cases ranging from the French Revolution to the abolition of slavery.
Keywords: Culture.; Social change.; Social values.; Social movements.; Social Values; Culture; Social Change; Changement social.; Valeurs sociales.; Mouvements sociaux.; social movements.; culture note.; culture (concept); POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; SOCIAL SCIENCE -- Sociology -- General.; Social change; Social movements; Social values; Culturele waarden.; Sociale verandering.; Cultuurverandering.